MICROWAVE AND INFRARED DRYING KINETICS AND ENERGY CONSUMPTION OF CHERRY TOMATOES - Kipcak, Azmi Seyhun; Doymaz, Ibrahim (ASSOC CHEMICAL ENG, 2020)
In this study, the effect of different microwave and infrared power levels on drying kinetics of cheny tomatoes is investigated Doting experiments are carried out with the power levels of 90, 180, 270 and 360 W (5.625, 11.250, 16.875 and 22500 W/g as power density) in microwave studies and 74, 83 and 104 W (0.871, 0.976 and 1.224 W/g as power density) in infrared studies. The obtained experimental moisture ratios are fitted to seven different widely used thin-layer models and the results showed that Weibull and Aghbashlo et al. models best fit the data for microwave and infrared doting of cheny tomatoes. The effective moisture diffusivities for microwave and infrared drying studies are calculated between 546 x 10(-8) and 4.24 x 10(-7) m(2)/s and 7.33 x 10(-9) - 8.24 x 10(-9) m(2)/s, respectively. Additionally, microwave and infrared activation energies are found to be 9.4654 and 0.3162 kW/kg, respectively.
Keywords: cherry tomato; drying kinetics; infrared drying; microwave drying; effective moisture diffusivity; activation energy; VACUUM-MICROWAVE; AIR; QUALITY; PRETREATMENT; DEHYDRATION; SLICES; Chemistry; Engineering